New GABA amides activating GABAA-receptors - Raster, Peter; Späth, Andreas; Bultakova, Svetlana; Gorostiza, Pau; König, Burkhard; Bregestovski, Piotr (Beilstein Journal of Organic Chemistry, 2013)
We have prepared a series of new and some literature-reported GABA-amides and determined their effect on the activation of GABAA-receptors expressed in CHO cells. Special attention was paid to the purification of the target compounds to remove even traces of GABA contaminations, which may arise from deprotection steps in the synthesis. GABA-amides were previously reported to be partial, full or superagonists. In our hands these compounds were not able to activate GABAA-receptor channels in whole-cell patch-clamp recordings. New GABA-amides, however, gave moderate activation responses with a clear structure–activity relationship suggesting some of these compounds as promising molecular tools for the functional analysis of GABAA-receptors.
Keywords: CHO-cells; GABA; GABA-amides; GABA-superagonist; patch-clamp recording